Kontekstualisi Pemikiran Sayyed Hossein Nasr Tentang Pendidikan Islam - Akhsanudin, M. (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Contextualization of Sayyed Hossein Nasr's thoughts in the world of education is very important because it helps ensure that educational ideas and principles proposed by a thinker or figure can be applied effectively in different situations and environments. This research uses a library research approach with qualitative research methods. Sayyed Hossein Nasr is a prominent Islamic philosopher and scholar who was born in 1933 in Tehran, Iran. As a major figure in the Perennialism philosophical tradition, Nasr believed in the existence of eternal truths that underlie all religious traditions. He emphasized the concept of Scientia Sacra or